Mathematics anxiety: Its assessment, determinants and remedies - Deieso, D.; Fraser, Barry (2018)
© 2018 Nova Science Publishers, Inc. All rights reserved. The widespread and debilitating effects of mathematics anxiety are experienced at all educational levels and in most countries around the world. This chapter illuminates this problem for educators and suggests ways to reduce mathematics anxiety among their students. First, the chapter describes, and provides a copy of, an economical, reliable and widely-applicable questionnaire for assessing students' mathematics anxiety. Second, we briefly report our research into some determinants of mathematics anxiety which suggests that students' levels of mathematics anxiety vary with student gender and grade level (with mathematics anxiety being higher for females and increasing across the transition from elementary to junior-high school). Third, some practical suggestions are proposed for educators to implement in order to alleviate mathematics anxiety among their students.